The impact of water regimes on hormesis by glyphosate on common bean - da Silva, Juliano Costa [UNESP]; Gerlach, Gustavo Antonio Xavier [UNESP]; Rodrigues, Ricardo Antonio Ferreira [UNESP]; Arf, Orivaldo [UNESP] (My University, 2016)
One way to induce the phenomenon of hormesis in plants is to use low herbicide doses. However, because results are not very conclusive, there is the hypothesis that hydric conditions during the crop cycle may influence the results. The present study therefore sought to evaluate the effect of low glyphosate doses on the irrigated common bean subjected to different water regimes. The experimental design consisted of randomized blocks arranged in a 3 x 2 factorial, with the treatments consisting of combinations of three glyphosate doses [0, 10 and 15 g acid equivalent (AE) ha-1] and two water conditions [355 and 391 mm (distributed according to the kc values for each phenological stage of the crop)], with four replications. The study was conducted under field conditions at the experimental farm of the State University of São Paulo-UNESP, Ilha Solteira campus, located in the city of Selvíria-MS, Brazil. The variables measured were: a) plant dry matter; b) nitrogen content in the leaves; c) number of pods plant-1; d) number of grains plant-1; e) number of grains pod-1; f) mass of 100 grains and g) grain yield. It may be concluded that hydric conditions during the crop cycle of the common bean have a great influence on the results of hormesis by glyphosate. In the presence of low glyphosate doses, the common bean demonstrated greater tolerance to hydric stress.
Keywords: Hormetic effect; Low herbicide doses; Phaseolus vulgaris L.; Water deficit